Respuesta :
Answer:
see explanation
Step-by-step explanation:
Using the rules of logarithms
log [tex]x^{n}[/tex] ⇔ n log x
log x + log y ⇔ log xy
Given
[tex]log_{a}[/tex] x + [tex]\frac{1}{2}[/tex] [tex]log_{a}[/tex] y
= [tex]log_{a}[/tex] x + [tex]log_{a}[/tex] [tex]y^{\frac{1}{2} }[/tex]
= [tex]log_{a}[/tex] (x [tex]y^{\frac{1}{2} }[/tex] )
= [tex]log_{a}[/tex] ( x[tex]\sqrt{y}[/tex] )
Answer: [tex]\bold{log_a(xy^{\frac{1}{2}})}[/tex]
Step-by-step explanation:
[tex]log_a(x)+\dfrac{1}{2}log_a(y)\\\\\text{Use the rules for condensing}\\\bullet \text{coefficient becomes exponent}\\\bullet \text{addition becomes multiplication}\\\\.\quad log_a(x)+log_a(y)^{\frac{1}{2}}\\= log_a[(x)(y)^\frac{1}{2}]\\= log_a(xy^{\frac{1}{2}})\\\\\\\text{This can also be written as: }log_a(x\sqrt{y})[/tex]